[1992] Proceedings 17th Conference on Local Computer Networks
DOI: 10.1109/lcn.1992.228168
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia over FDDI

Abstract: This paper focuses on issues in multimedia networking over FDDI and simulation results demonstrating the feasibility of multimedia over FDDI. Previous work in this field has concentrated on the asynchronous channel in FDDI. Other examinations of the FDDI synchronous channel have applied bursty tr&c to the synchronous channel. Multimedia trajjk is typically stream oriented.Our simulations were focused on simulating typical configurations with a range of applications and traffic models. The advantages of FDDI as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It is because the human eye can hardy recognize a frame which is out of synchronization within 3 frame-time --that is 1/10 second. Studies by Shah et al [SHA92] have shown that our vision system will recognize a sequence of frames as distinct pictures if the display rate is at 8 frames per second or lower. Between 10 to 12 frames per second, the frame sequence would appear to be choppy.…”
Section: The Regulated Schemementioning
confidence: 99%
“…It is because the human eye can hardy recognize a frame which is out of synchronization within 3 frame-time --that is 1/10 second. Studies by Shah et al [SHA92] have shown that our vision system will recognize a sequence of frames as distinct pictures if the display rate is at 8 frames per second or lower. Between 10 to 12 frames per second, the frame sequence would appear to be choppy.…”
Section: The Regulated Schemementioning
confidence: 99%
“…The phenomenon has been studied extensively, however, for participants in interactive phone conversations [35], and these results provide rst-order information on the delays acceptable in other interactive applications. Table 1.1 gives a summary of the eects of roundtrip delay on speech quality (adapted from [53]). In general, high-quality voice applications require less than 200 ms roundtrip delays, but delays of up to 600 ms have been shown to be acceptable [35].…”
Section: Roundtrip Delaymentioning
confidence: 99%
“…This application involves the transmission of audio, visual and textual instructions. The total traffic volume for each multimedia session is 6.877 Mbps [22] . Figure 2 shows the maximum number of multimedia sessions a network protocol can support at various data transfer rates.…”
Section: Simulation Experimentsmentioning
confidence: 99%
“…This application also contains audio and textual data. The total traffic volume per multimedia session is 3.594 Mbps [22] . The traffic volume for this application is almost half of that for the interactive educationltraining application.…”
Section: Interactive Education / Trainingmentioning
confidence: 99%
See 1 more Smart Citation